Metafora Konseptual Duka pada Album Folklore Karya Taylor Swift melalui Lensa Kübler-Ross - Suci Ayustika Dewi; Gusthini, Misyi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study analyzes the use of conceptual metaphors representing the grieving process in Taylor Swift's album "Folklore" through the lens of Kübler-Ross's five stages of grief. The method employed is a qualitative descriptive approach, with data collection conducted through the analysis of song lyrics obtained from physical albums and digital music platforms. The research instrument consists of a guideline for identifying and categorizing metaphors related to the theme of grief. The data analysis procedure includes in-depth reading to identify metaphors, which are then categorized according to the stages of grief. The findings indicate that each song in the album reflects various aspects of denial, anger, bargaining, depression, and acceptance, providing a profound understanding of the grieving experience. This research demonstrates that metaphors in the lyrics serve not only as artistic expression but also as a means to comprehend the psychological processes individuals undergo. The study recommends further analysis of other albums with similar themes to enrich the understanding of the emotional impact of song lyrics